Study on the Development of Explosive Force in Athletic Jumping through Plyometrics Exercises at the Level of Junior Athletes - I. Samson; F. Nechita (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The purpose of this article is to demonstrate the importance of implementing plyometric exercises especially in the case of students in vocational mainstream education for improving relaxation and implicitly sports performance. The present paper highlights a study based on a theoretical and practical approach to the notion of plyometrics by applying a specific program based on plyometric exercises for the development of explosive force in advanced groups, compared to subjects carrying out a regular training program. By implementing this type of exercise at the level of all students, regardless of the way in which they practice athletics, benefits are brought both in terms of sports performance and health.